Method for recovering peptizing property of modified pseudo-boehmite and application thereof

By combining the modification treatment and fumigation method of phthalinite, its gelatinization is successfully restored and the pore structure is improved, the problem of poor gelatinization after modification is solved, and the production of high-performance catalysts and supports is realized.

CN119797402APending Publication Date: 2025-04-11PETROCHINA CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311303943.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

After modification, the existing pseudo-thin water-aluminite has poor gel solubility and poor pore structure, which affects the performance of the catalyst and support.

Method used

After mixing the pseudo-thin aluminite with a modifier, undergoing solid phase reaction and calcination treatment, the fumigation method is used to treat it at 60-110°C to restore its gelatinous solubility and improve the pore structure.

Benefits of technology

The peptosis index of phthalidite was significantly improved from 14.32% to 95.39%, and the specific surface area and pore volume were improved to meet the requirements of industrial catalyst support and binders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797402A_ABST
    Figure CN119797402A_ABST
Patent Text Reader

Abstract

The invention discloses a recovery method of peptization of modified pseudo-boehmite and application thereof, and the recovery method of peptization of modified pseudo-boehmite comprises the following steps: (1) uniformly mixing pseudo-boehmite and a modifier, and carrying out solid-phase reaction to obtain an alumina precursor sample; (2) putting the aluminum oxide precursor sample into a closed container, adding deionized water, fumigating at 60-110 DEG C for 12-30 hours, and drying; or (1) uniformly mixing pseudo-boehmite and a modifier, carrying out solid-phase reaction to obtain an aluminum oxide precursor, and roasting the aluminum oxide precursor; and (2) putting the roasted sample into a closed container, adding deionized water, fumigating at 60-110 DEG C for 12-30 hours, and drying. According to the method disclosed by the invention, the modified pseudo-boehmite has a developed pore structure while the peptizing property is recovered, and the method disclosed by the invention is green, environment-friendly, simple in process and relatively low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for recovering the colloidal solubility of modified pseudo-boehmite and application thereof. Background Art

[0002] Pseudo-boehmite is a powder with low crystallinity and spatial network structure, which is usually considered to be incompletely crystallized boehmite. It can react with nitric acid, hydrochloric acid, trichloroacetic acid, etc. to form aluminum sol, which is widely used as a binder, especially in the field of catalysis. It can be used as a binder for catalytic materials such as molecular sieves and alumina, and can also be used alone as a raw material for catalyst carriers. However, the pseudo-boehmite synthesized by different preparation processes has significant differences in colloidal solubility, which has different effects on the performance of catalysts or carriers.

[0003] Alumina has the advantages of high melting point, high hardness, excellent catalytic performance, good thermal stability, good corrosion resistance, and excellent photoelectric performance. Pseudoboehmite is a precursor of alumina. Different preparation processes can obtain alumina with different properties to meet the needs of various fields. At present, the commonly used processes include the modified Bayer process, inorganic aluminum salt thermal decomposition method, organic alcohol aluminum salt hydrolysis method, hydrothermal synthesis method, etc. Among them, the pseudoboehmite synthesized by the alcohol aluminum method has the highest purity. However, its pore structure is poor, with a specific surface area of ​​about 300m 2 / g, pore volume about 0.4cm 3 / g, thus affecting the dispersion of active components and the diffusion performance of the catalyst. Pseudo-boehmite can be prepared at room temperature by thermal decomposition of inorganic aluminum salts. The process is simple and the production cost is low, but the gel solubility is uncontrollable, the sol impurity content is high, the sol purity is low, and the specific surface area is about 200m 2 / g, pore volume is about 0.4cm 3 / g, the catalyst stability is poor.

[0004] The peptization principle of pseudo-boehmite is to use the H+ in the "acid" to react with the hydroxyl groups on the surface of pseudo-boehmite to form particles with positive charges on the surface. By forming an "acid bridge" between the positively charged particles, multiple pseudo-boehmite particles are connected together in a network form, so that the pseudo-boehmite particles lose fluidity and become peptized. The peptization property of pseudo-boehmite is an external manifestation of its internal structure. In the microstructure of pseudo-boehmite, interlayer water is connected to the hydroxyl groups in the Al-O octahedron in the form of hydrogen bonds. Due to the presence of interlayer water, the Al-O distance increases and the Al-OH (hydroxyl) distance becomes shorter, resulting in unit cell stacking faults and lattice distortion, making it easy to react with acids to peptize. At present, most industrial catalysts need to have high mechanical strength, and the peptization solubility of pseudo-boehmite directly determines the mechanical strength of the carrier. Therefore, it is of great significance to improve the peptization solubility of pseudo-boehmite.

[0005] The currently synthesized pseudo-boehmite has good peptization solubility, but poor pore structure, while the modified pseudo-boehmite generally has a high specific surface area and large pore volume, but poor peptization solubility. Therefore, it is of great significance to synthesize pseudo-boehmite with high specific surface area, large pore volume and good peptization solubility by a mild condition and low cost method. Summary of the invention

[0006] In view of the defects in the prior art, the present invention provides a method for recovering the colloidal solubility of modified pseudo-boehmite, so as to at least partially solve the problems existing in the prior art.

[0007] In a first aspect, the present invention provides a method for recovering the colloidal solubility of modified pseudo-boehmite, comprising:

[0008] (1) After the pseudo-boehmite and the modifier are uniformly mixed, a solid phase reaction is performed to obtain an alumina precursor sample;

[0009] (2) placing the alumina precursor sample in a sealed container, adding deionized water, fumigating at 60 to 110° C. for 12 to 30 hours, and then drying;

[0010] or,

[0011] (1) After the pseudo-boehmite and the modifier are uniformly mixed, a solid phase reaction is carried out to obtain an alumina precursor, and then the alumina precursor is calcined;

[0012] (2) Place the calcined sample in a sealed container, add deionized water, fumigate at 60-110°C for 12-30 hours, and then dry it.

[0013] In one or some optional embodiments, the mass ratio of the modifier to pseudo-boehmite is 1 to 10:1.

[0014] In one or some preferred embodiments, the mass ratio of the modifier to pseudo-boehmite is 1 to 5:1.

[0015] In one or some optional embodiments, the modifier is two of ammonium salts (such as ammonium nitrate, ammonium carbonate, ammonium bicarbonate, ammonium carbamate, ammonium formate, ammonium oxalate, etc.) or amide compounds (such as formamide, acetamide, urea, etc.).

[0016] In one or some optional embodiments, the mass ratio of the modifier is 1 to 5:1.

[0017] In one or some preferred embodiments, the mass ratio of the modifier is 1 to 2:1.

[0018] In one or some optional embodiments, the crystallization temperature of the solid phase reaction is 80-120° C., and the crystallization time is 18-36 hours.

[0019] In one or some preferred embodiments, the crystallization temperature of the solid phase reaction is 90-110° C., and the crystallization time is 24-36 hours.

[0020] In one or some optional embodiments, the calcination temperature is 200-300°C.

[0021] In one or some preferred embodiments, the calcination temperature is 300°C.

[0022] In one or some optional embodiments, the mass ratio of the deionized water to the sample is 20 to 60:1.

[0023] In one or some preferred embodiments, the mass ratio of the deionized water to the sample is 20-40:1.

[0024] In one or some preferred embodiments, the fumigation temperature is 70-100° C., and the fumigation time is 12-24 hours.

[0025] In a specific embodiment, the fumigation method is to place the alumina precursor into a tubular furnace or a closed container, and the steam flow direction can be a bottom-up flow type, a horizontal flow type, or a top-down flow type, among which the bottom-up flow type is the best.

[0026] In one or some optional embodiments, the drying temperature is 50-200° C., and the drying time is 6-48 hours.

[0027] In one or some preferred embodiments, the drying temperature is 80-100° C., and the drying time is 12-24 hours.

[0028] In a second aspect, the present invention provides application of the above method in producing catalyst carriers and binders.

[0029] The method of the present invention takes the peptization solubility of the raw material pseudo-boehmite as the benchmark. The peptization index of the sample after fumigation is as high as 95.39%, which is 81 percentage points higher than the peptization index of the sample before fumigation, which is 14.32%. Compared with the raw material pseudo-boehmite, the specific surface area of ​​the sample after fumigation is increased from 283.7m 2 / g increased to 480.8m 2 / g, pore volume from 0.38cm 3 / g increased to 1.03cm 3 / g. Compared with the sample before fumigation, the specific surface area of ​​the sample after fumigation increased from 534.3m 2 / g dropped to 480.8m 2 / g, pore volume from 1.31cm3 / g dropped to 1.03cm 3 / g, with a small decrease. Compared with pseudo-boehmite, the pore structure of the fumigated sample is significantly improved; compared with the sample before fumigation, the peptization solubility is restored, and at the same time, it meets the requirements of industrial production of catalyst carriers and binders.

[0030] Considering that the hydroxyl content between pseudo-boehmite layers is an important factor affecting the peptization solubility of pseudo-boehmite, the method of the present invention directly supplements hydroxyl groups to basic ammonium aluminum carbonate by fumigation, or supplements hydroxyl groups to alumina obtained after AACH is roasted, so that AACH and alumina are converted into pseudo-boehmite crystal phases, so that it has a developed pore structure while restoring peptization solubility, thereby achieving high mechanical strength and high reaction activity of industrial catalyst pellets. The method of the present invention has green and environmentally friendly alumina precursor synthesis process and peptization solubility restoration process, simple process, mild conditions, low cost, and strong practical application significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 N2 adsorption-desorption isotherms of the modified pseudo-boehmite obtained in Examples 1-3 and Comparative Examples 1-3 of the present invention;

[0032] Figure 2 The pore size distribution curves of the modified pseudo-boehmite obtained in Examples 1-3 and Comparative Examples 1-3 of the present invention are shown;

[0033] Figure 3 XRD diffraction patterns of the modified pseudo-boehmite obtained in Examples 1-3 and Comparative Examples 1-3 of the present invention;

[0034] Figure 4 N2 adsorption-desorption isotherms of the modified pseudo-boehmite obtained in Examples 4-5 and Comparative Examples 4-5 of the present invention;

[0035] Figure 5 The pore size distribution curves of the modified pseudo-boehmite obtained in Examples 4-5 and Comparative Examples 4-5 of the present invention are shown;

[0036] Figure 6 The XRD diffraction patterns of the modified pseudo-boehmite obtained in Examples 4-5 and Comparative Examples 4-5 of the present invention are shown. DETAILED DESCRIPTION

[0037] The following is a detailed description of the embodiments of the present invention: The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters for which specific conditions are not specified in the following embodiments are generally based on conventional conditions.

[0038] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0039] Basic ammonium aluminum carbonate (AACH) is often used as a precursor for producing high specific surface area alumina. The inventors referred to the patent CN111233017 A, a process for synthesizing monoclinic basic ammonium aluminum carbonate and pyrolyzing it to prepare porous alumina, and used solid phase reaction to obtain a new compound - monoclinic basic ammonium aluminum carbonate. The material has a high specific surface area (631.9 m 2 / g) and macropore volume (1.9 cm 3 / g), but the material has poor peptization solubility, and the peptization index of the synthesized AACH is only 8% to 9% of that of the raw material; it cannot meet the requirements of industrial binders and carriers. The inventors used the synthesis of monoclinic basic ammonium aluminum carbonate and its pyrolysis to prepare porous alumina with reference to patent CN111233017A, but the material synthesized by this method has poor peptization solubility and does not meet the requirements of industrial binders. The inventors prepared a high-viscosity pseudo-boehmite with reference to patent CN112479240 A, but the pore structure of the synthesized high-viscosity pseudo-boehmite was poor.

[0040] In view of the fact that the above mentioned methods failed to meet the inventor's expectations, the inventor made the present invention after further research and development.

[0041] Example 1

[0042] At room temperature, ammonium nitrate and ammonium carbonate in a mass ratio of 1:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed according to a mass ratio of modifier to pseudo-boehmite powder (SB powder) of 2.5:1, and fully ground with a mortar for 30 minutes, mixed evenly, and the mixed solid powder was transferred to a 100ml closed crystallization kettle, reacted at 110°C for 24 hours, and the solid obtained after the reaction was dried at 80°C for 24 hours. The dried sample was placed in a vertical tube furnace, and N2 was bubbled in 70°C deionized water and then entered the tube furnace from bottom to top, with a steam flow rate of 0.1L / h, fumigated for 12 hours, and the fumigated sample was dried at 80°C for 24 hours to obtain the modified pseudo-boehmite, which was recorded as A-1. The specific surface area and pore volume were detected by N2 physical adsorption instrument as shown in Table 3.

[0043] The modified pseudo-boehmite was vacuum degassed at 300 °C, and the sample was tested at liquid nitrogen temperature (77K) with high-purity nitrogen as the adsorbent. The adsorption amount changed with the increase of relative pressure. The BET (Brunauer-Emmett-Teller) method was used to obtain its N2 adsorption-desorption isotherm. Figure 1 As shown; the pore size distribution curve obtained by the BJH (Barrett-Joiner-Halenda) method is as follows Figure 2 As shown; the synthesized sample was analyzed by X-ray diffractometer, with Cu, Kα ray as the diffraction source, the diffraction wavelength was 0.154nm, the operating current was 40mA and the operating voltage was 40kV, the scanning range was 5-75°, and the XRD diffraction pattern was obtained as shown Figure 3 shown.

[0044] Weigh 5 g of A-1 and heat it to 800°C at a rate of 5°C / min in a muffle furnace, keep the temperature constant for 2 hours, and naturally cool to room temperature. The mass of the sample is weighed and recorded as m2, and the alumina mass fraction of A-1 is obtained as ω=m2 / 5×100%.

[0045] Weigh 15g A-1 in a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid in a 50ml crucible, dry at 100℃ for 24h, place the dried sample in a muffle furnace and heat to 800℃ at a rate of 5℃ / min, keep the temperature constant for 2h, cool naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-1 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 1.

[0046] Comparative Example 1

[0047] At room temperature, ammonium nitrate and ammonium carbonate in a mass ratio of 1:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed according to a mass ratio of modifier to pseudo-boehmite powder (SB powder) of 2.5:1. The powder was fully ground in a mortar for 30 minutes and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle and reacted at 110°C for 24 hours. The solid obtained after the reaction was dried at 80°C for 24 hours to obtain modified pseudo-boehmite, which was recorded as A-2. The specific surface area and pore volume were detected by a N2 physical adsorption instrument as shown in Table 3.

[0048] Weigh 5g of A-2 and place it in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min. Keep it at this temperature for 2h and cool it naturally to room temperature. Weigh the mass of the sample and record it as m2. The alumina mass fraction of A-2 is ω=m2 / 5×100%.

[0049] Weigh 15g A-2 into a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid into a 50ml crucible, dry it at 100℃ for 24h, place the dried sample in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h, cool it naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-2 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 1.

[0050] Example 2

[0051] At room temperature, ammonium carbonate and ammonium oxalate with a mass ratio of 2:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed according to a mass ratio of 5:1 between the modifier and pseudo-boehmite powder, and the powder was fully ground with a mortar for 30 minutes and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle, reacted at 90°C for 24 hours, and the solid obtained after the reaction was dried at 80°C for 24 hours. The dried sample was placed in a vertical tube furnace, and N2 was bubbled in 80°C deionized water and then entered the tube furnace from top to bottom at a flow rate of 0.1L / h. The steam fumigation was performed for 12 hours, and the fumigated sample was dried at 70°C for 24 hours. The fumigated sample was dried at 80°C for 24 hours to obtain the modified pseudo-boehmite, which was recorded as A-3. The specific surface area and pore volume were detected by N2 physical adsorption instrument as shown in Table 3.

[0052] Weigh 5g of A-3 and heat it to 800℃ at a rate of 5℃ / min in a muffle furnace, keep it constant for 2h, and naturally cool it to room temperature. Weigh the mass of the sample and record it as m2. The alumina mass fraction of A-3 is obtained as ω=m2 / 5×100%.

[0053] Weigh 15g A-3 in a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid in a 50ml crucible, dry at 100℃ for 24h, place the dried sample in a muffle furnace and heat to 800℃ at a rate of 5℃ / min, keep the temperature constant for 2h, cool naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-3 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 1.

[0054] Comparative Example 2

[0055] At room temperature, ammonium carbonate and ammonium oxalate in a mass ratio of 2:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed according to a mass ratio of modifier to pseudo-boehmite powder (SB powder) of 5:1. The powder was fully ground in a mortar for 30 minutes and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle and reacted at 90°C for 24 hours. The solid obtained after the reaction was dried at 80°C for 24 hours to obtain modified pseudo-boehmite, which was recorded as A-4. The specific surface area and pore volume were detected by N2 physical adsorption instrument as shown in Table 3.

[0056] Weigh 5g of A-4 and place it in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min. Keep it at this temperature for 2h and cool it naturally to room temperature. Weigh the mass of the sample and record it as m2. The alumina mass fraction of A-4 is ω=m2 / 5×100%.

[0057] Weigh 15g A-4 into a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid into a 50ml crucible, dry it at 100℃ for 24h, place the dried sample in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h, cool it naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-4 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 1.

[0058] Example 3

[0059] At room temperature, ammonium nitrate and urea in a mass ratio of 2:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed according to a mass ratio of modifier to pseudo-boehmite powder (SB powder) of 10:1. The powder was fully ground for 30 minutes using a ball mill and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle, reacted at 100 ° C for 36 hours, and the solid obtained after the reaction was dried at 100 ° C for 24 hours. The dried sample was placed on a sieve covered with a layer of filter paper, and placed in a 3.5L polytetrafluoroethylene liner filled with deionized water with a liquid level lower than the sample height. The liner was sealed with plastic wrap, fumigated in an oven at 90 ° C for 18 hours, and the fumigated sample was dried at 80 ° C for 30 hours to obtain the modified pseudo-boehmite, which was recorded as A-5. The specific surface area and pore volume were detected by N2 physical adsorption instrument as shown in Table 3.

[0060] Weigh 5g of A-5 and heat it to 800℃ at a rate of 5℃ / min in a muffle furnace, keep it at this temperature for 2h, and naturally cool it to room temperature. The mass of the sample is weighed and recorded as m2, and the alumina mass fraction of A-5 is obtained as ω=m2 / 5×100%.

[0061] Weigh 15g A-5 in a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid in a 50ml crucible, dry at 100℃ for 24h, place the dried sample in a muffle furnace and heat to 800℃ at a rate of 5℃ / min, keep the temperature constant for 2h, cool naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-5 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 1.

[0062] Comparative Example 3

[0063] At room temperature, ammonium nitrate and urea in a mass ratio of 2:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed according to a mass ratio of modifier to pseudo-boehmite powder (SB powder) of 10:1. The powder was fully ground with a ball mill for 30 minutes and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle and reacted at 100 °C for 36 hours. The solid obtained after the reaction was dried at 100 °C for 24 hours to obtain modified pseudo-boehmite, which was recorded as A-6. The specific surface area and pore volume were detected by N2 physical adsorption instrument as shown in Table 3.

[0064] Weigh 5g of A-6 and place it in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min. Keep it at this temperature for 2h and cool it naturally to room temperature. Weigh the mass of the sample and record it as m2. The alumina mass fraction of A-6 is ω=m2 / 5×100%.

[0065] Weigh 15g A-6 into a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid into a 50ml crucible, dry it at 100℃ for 24h, place the dried sample in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h, cool it naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-6 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 1.

[0066] Example 4

[0067] At room temperature, ammonium bicarbonate and ammonium nitrate in a mass ratio of 1:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed at a mass ratio of 7.5:1. The modified powder was fully ground in a ball mill for 30 minutes and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle, reacted at 100 ° C for 30 hours, and the reacted sample was dried at 80 ° C for 30 hours. After drying, it was placed in a muffle furnace and heated to 200 ° C at 2 ° C / min for roasting, kept at a constant temperature for 4 hours, and naturally cooled to room temperature. The cooled sample was placed in a horizontal tube furnace, and N2 was bubbled in 100 ° C deionized water and then flowed horizontally into the tube furnace at a flow rate of 0.1 L / h. The sample was steam fumigated at 100 ° C for 18 hours. The fumigated sample was dried at 90 ° C for 24 hours to obtain the modified pseudo-boehmite, which was recorded as A-7. The specific surface area and pore volume were measured by N2 physical adsorption instrument as shown in Table 3.

[0068] Weigh 5g of A-7 and heat it to 800℃ at a rate of 5℃ / min in a muffle furnace, keep it constant for 2h, and naturally cool it to room temperature. The mass of the sample is weighed and recorded as m2, and the alumina mass fraction of A-7 is obtained as ω=m2 / 5×100%.

[0069] Weigh 15g A-7 in a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid in a 50ml crucible, dry at 100℃ for 24h, place the dried sample in a muffle furnace and heat to 800℃ at a rate of 5℃ / min, keep the temperature constant for 2h, cool naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-7 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 2.

[0070] Comparative Example 4

[0071] At room temperature, ammonium bicarbonate and ammonium nitrate in a mass ratio of 1:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed at a mass ratio of 7.5:1. The powder was fully ground in a ball mill for 30 minutes and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle and reacted at 100 °C for 30 hours. The reacted sample was dried at 80 °C for 30 hours, and then placed in a muffle furnace and heated to 200 °C at 2 °C / min. The temperature was maintained for 4 hours and naturally cooled to room temperature to obtain the modified pseudo-boehmite, which was recorded as A-8. The specific surface area and pore volume were detected by N2 physical adsorption instrument as shown in Table 3.

[0072] Weigh 5g of A-8 and place it in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min. Keep it at this temperature for 2h and cool it naturally to room temperature. Weigh the mass of the sample and record it as m2. The alumina mass fraction of A-8 is ω=m2 / 5×100%.

[0073] Weigh 15g A-8 into a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid into a 50ml crucible, dry it at 100℃ for 24h, place the dried sample in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h, cool it naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-8 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 2.

[0074] Example 5

[0075] At room temperature, ammonium formate and ammonium carbonate in a mass ratio of 2:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed at a mass ratio of 7.5:1. The powder was fully ground for 30 min using a ball mill and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle and reacted at 100 °C for 24 h. The reacted sample was dried at 90 °C for 30 h, and then placed in a muffle furnace and heated at 2 °C / min to The sample was calcined at 300 °C for 4 h and cooled naturally to room temperature. The cooled sample was placed on a sieve covered with a layer of filter paper and placed in a 3.5 L polytetrafluoroethylene liner filled with deionized water with the liquid level lower than the sample height. The liner was sealed with plastic wrap and fumigated in an oven at 90 °C for 24 h. The fumigated sample was dried at 80 °C for 30 h to obtain the modified pseudo-boehmite, recorded as A-9. The specific surface area and pore volume were detected by N2 physical adsorption instrument as shown in Table 3.

[0076] Weigh 5g of A-9 and heat it to 800℃ at a rate of 5℃ / min in a muffle furnace, keep the temperature constant for 2h, and naturally cool to room temperature. The mass of the sample is weighed and recorded as m2, and the alumina mass fraction of A-9 is obtained as ω=m2 / 5×100%.

[0077] Weigh 15g A-9 in a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid in a 50ml crucible, dry at 100℃ for 24h, place the dried sample in a muffle furnace and heat to 800℃ at a rate of 5℃ / min, keep the temperature constant for 2h, cool naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-9 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 2.

[0078] Comparative Example 5

[0079] At room temperature, ammonium formate and ammonium carbonate in a mass ratio of 2:1 were weighed as modifiers, and pseudo-boehmite powder (SB powder) was weighed at a mass ratio of 7.5:1. The powder was fully ground in a ball mill for 30 minutes and mixed evenly. The mixed solid powder was transferred to a 100 ml closed crystallization kettle and reacted at 100 ° C for 24 hours. The reacted sample was dried at 90 ° C for 30 hours, and then placed in a muffle furnace and heated to 300 ° C at 2 ° C / min. The temperature was kept constant for 4 hours and naturally cooled to room temperature to obtain the modified pseudo-boehmite, which was recorded as A-10. The specific surface area and pore volume were detected by N2 physical adsorption instrument as shown in Table 3.

[0080] Weigh 5g of A-10 and place it in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min. Keep it at this temperature for 2h and cool it naturally to room temperature. Weigh the mass of the sample and record it as m2. The alumina mass fraction of A-10 is ω=m2 / 5×100%.

[0081] Weigh 15g A-10 in a 50ml beaker, add (ω×100-10)g deionized water to prepare a pseudo-boehmite suspension with a mass fraction of 10% (calculated as alumina); add (15×ω×0.32)g concentrated nitric acid (mass fraction of 65%), and stir electromagnetically for 15min; transfer the formed suspension to a 50ml centrifuge tube, centrifuge at a rate of 5000r / min for 30min, take the upper colloidal liquid in a 50ml crucible, dry it at 100℃ for 24h, place the dried sample in a muffle furnace and heat it to 800℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h, cool it naturally to room temperature, weigh the remaining sample mass and record it as m3, and the peptization index of A-10 is (m3 / 15ω)×100%. The specific values ​​are shown in Table 2.

[0082] Table 1

[0083] sample A-1 A-2 A-3 A-4 A-5 A-6 Pseudo-boehmite powder Peptization index 60.60% 8.45% 66.32% 9.58% 95.39% 14.32% 1

[0084] Table 2

[0085] sample A-7 A-8 A-9 A-10 Pseudo-boehmite powder Peptization index 71.57% 5.68% 84.55% 2.15% 1

[0086] Table 3

[0087]

[0088]

[0089] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art. According to all the teachings disclosed, various modifications and replacements can be made to those details, and these changes are all within the protection scope of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.

Claims

1. A method for restoring the colloidal solubility of modified pseudo-boehmite, characterized in that: include: (1) After the pseudo-boehmite and the modifier are uniformly mixed, a solid phase reaction is performed to obtain an alumina precursor sample; (2) placing the alumina precursor sample in a sealed container, adding deionized water, fumigating at 60 to 110° C. for 12 to 30 hours, and then drying; or, (1) After the pseudo-boehmite and the modifier are uniformly mixed, a solid phase reaction is carried out to obtain an alumina precursor, and then the alumina precursor is calcined; (2) Place the calcined sample in a sealed container, add deionized water, fumigate at 60-110°C for 12-30 hours, and then dry it.

2. The method according to claim 1, characterized in that The mass ratio of the modifier to pseudo-boehmite is 1 to 10:

1.

3. The method according to claim 2, characterized in that The optimal mass ratio of the modifier to pseudo-boehmite is 1 to 5:

1.

4. The method according to claim 1, characterized in that The modifier is two of ammonium salts or amide compounds.

5. The method according to claim 4, characterized in that The mass ratio of the modifier is 1 to 5:

1.

6. The method according to claim 5, characterized in that The mass ratio of the modifier is 1 to 2:

1.

7. The method according to claim 1, characterized in that The crystallization temperature of the solid phase reaction is 80-120° C., and the crystallization time is 18-36 hours.

8. The method according to claim 7, characterized in that The optimal crystallization temperature of the solid phase reaction is 90-110° C., and the optimal crystallization time is 24-36 hours.

9. The method according to claim 1, characterized in that The calcination temperature is 200-300°C.

10. The method according to claim 9, characterized in that The calcination temperature is 300°C.

11. The method according to claim 1, characterized in that The mass ratio of the deionized water to the sample is 20 to 60:

1.

12. The method according to claim 11, characterized in that The optimal mass ratio of the deionized water to the sample is 20-40:

1.

13. The method according to claim 1, characterized in that The optimal fumigation temperature is 70-100° C., and the optimal fumigation time is 12-24 hours.

14. The method according to claim 1, wherein: The drying temperature is 50-200° C., and the drying time is 6-48 hours.

15. The method according to claim 14, characterized in that The optimal drying temperature is 80-100° C., and the optimal drying time is 12-24 hours.

16. Use of the method according to any one of claims 1 to 15 in the production of catalyst carriers and binders.